2018
DOI: 10.3390/d10010016
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal Efficiency of Rhizophora mangle (L.) Seedlings Exposed to Experimental Dumping of Municipal Waters

Abstract: Mangrove forests are conspicuous components of tropical wetlands that sustain continuous exposure to wastewater discharges commonly of municipal origins. Mangroves can remove nutrients from these waters to fulfill their nutrients demand, although the effects of continuous exposure are unknown. An experimental greenhouse imitating tidal regimes was built to measure the efficiency of mangrove seedlings to incorporate nutrients, growth and above biomass production when exposed to three periodic wastewater dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Stagnation and evaporation increase the concentration of soil nutrients. The waterlogging and the decrease in topography from the basin towards the impaired site favor soil anaerobic conditions, increasing the concentration of reduced compounds such as sulfides, ammonium, and methane [49,[51][52][53][54][55][56][57]. The increase in organic matter and low soil density result from the loss of connectivity between the impaired site and the main tidal channel of Estero Pargo.…”
Section: Discussionmentioning
confidence: 99%
“…Stagnation and evaporation increase the concentration of soil nutrients. The waterlogging and the decrease in topography from the basin towards the impaired site favor soil anaerobic conditions, increasing the concentration of reduced compounds such as sulfides, ammonium, and methane [49,[51][52][53][54][55][56][57]. The increase in organic matter and low soil density result from the loss of connectivity between the impaired site and the main tidal channel of Estero Pargo.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the most urban mangroves are permanently or periodically flooded (0.001-2.5 times per day) by urban waters, which likely carry elevated nitrogen and phosphorus concentrations that have been tied to roads and sewage [76][77][78]. Such nutrient enrichment has been shown to increase girth but decrease height of mangrove seedlings [79], while the height of dwarf mangroves was found to increase with both nitrogen and phosphorus fertilization [80]. Thus, these nutrients likely influence urban mangrove growth depending upon antecedent conditions and their interaction with other water quality and flooding conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from the Forest Research Institute Malaysia (FRIM) revealed that Bakau minyak barks contain significant amounts of tannins, which is, however, subject to the method of extraction and type of solvents used (Sukardjo 1987). Rhizophora mucronata and Rhizophora mangle are common representatives of the Rhizophora family (Basyuni et al 2018;Ghazali et al 2018a, b, Vigneswaran et al 2018Maricusa et al 2018). Locally derived tannin-based Rhizophora mucronata is abundant in soft tissues form, such as leaves, needles and barks wastes (Vigneswaran et al 2018).…”
Section: Introductionmentioning
confidence: 99%